Factors Influencing Business Zakah Compliance Behavior among Moslem Businessmen in Malaysia: A Research Model. (31st May 2016) - Saad, Ram Al Jaffri; Wahab, Muhammad Syahir Abdul; Samsudin, Mohd. Amir Mat
Abstract: This paper aims to propose a research model for examining the influence of internal and external factors on Business Zakah compliance behavior among businessmen in Malaysia. An extensive literature review method was utilized to identify and analyze the relevant literatures in order to propose the model. This paper identified two internal and two external factors of the compliance behavior. The internal factors are knowledge and self-efficacy while service quality and interaction are the external factors. Theoretical and practical implications of the paper as well as suggestions for future research were also discussed.